2013
DOI: 10.12657/denbio.070.007
|View full text |Cite
|
Sign up to set email alerts
|

Differences among Juniperus excelsa populations as revealed at morphological traits

Abstract: Abstract:The comparison of phenotypic trait differentiation and genetic differentiation at selectively neutral genetic markers can indicate divergent selection on traits. Phenotypic trait differentiation (P ST ) and two multivariate analysis methods were used to determine the level of differentiation and relationships among seven Juniperus excelsa populations based on 13 morphological characters of their cones, seeds, juvenile seedlings and 1+0 year old seedlings. Significant differences among populations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Sufficient homogeneity was achieved within the blocks extending from uphill to downhill, and environmental differences among populations were minimized. Spacing between saplings was 2 × 3 m. Each population was represented by 30 saplings (10 saplings per block) grown from seeds in Egirdir Forest Nursery (Yücedag & Gailing 2013b). The total number of seedlings planted was 240.…”
Section: Experimental Designmentioning
confidence: 99%
“…Sufficient homogeneity was achieved within the blocks extending from uphill to downhill, and environmental differences among populations were minimized. Spacing between saplings was 2 × 3 m. Each population was represented by 30 saplings (10 saplings per block) grown from seeds in Egirdir Forest Nursery (Yücedag & Gailing 2013b). The total number of seedlings planted was 240.…”
Section: Experimental Designmentioning
confidence: 99%
“…The genetic quality of juniper's seed has not been yet well studied. Thus, to make some generalizations we are still relying on recent studies of gene flow and genetic diversity of adult juniper populations (Korshikov and Nikolaeva 2007, Yücedağ 2008, Hojjati et al 2009, Yücedağ et al 2010, Douaihy et al 2011, Gülsoy et al 2012, Korshikov and Nikolaeva 2013, Yücedağ and Gailing 2013a, 2013b, Pinna et al 2014, Saeed et al 2017, Yücedağ and Ozel 2017, Mazur et al 2018. Studies have shown that a reduction in stand density and isolation of individuals may enhance inbreeding.…”
Section: Seeds' Genetic Constraintsmentioning
confidence: 99%